EXPERIMENTAL SILICATE MINERAL/MELT PARTITION COEFFICIENTS FOR BERYLLIUM AND THE CRUSTAL BE CYCLE FROM MIGMATITE TO PEGMATITE - Evensen J.M.; London D. (My University, 2002)
Partition coefficients (DBemineral/melt) for beryllium between hydrous granitic melt and alkali feldspars, plagioclase feldspars, quartz, dark mica, and white mica were determined by experiment at 200 MPa H2O as a function of temperature (650–900°C), activity of Be in melt (trace levels to beryl saturation), bulk composition, and thermal run direction. At trace levels, Be is compatible in plagioclase of An31 (1.84 at 700°C) and muscovite (1.35 at 700°C) but incompatible in biotite (0.39–0.54 from 650–800°C), alkali feldspar (0.38–0.19 from 680–850°C), quartz (0.24 at 800°C), and albite (0.10 at 750°C). The partition coefficients are different at saturation of the melt in beryl: lower in the case of plagioclase of An31 (0.89 at 700°C), muscovite (0.87 at 700°C), biotite (0.18–0.08 from 675–800°C), alkali feldspar (0.18–0.14 from 680–700°C), and quartz (0.17–0.08 from 750–800°C), but higher in the case of albite (0.37 at 750°C).With other data sources, these new partition coefficients were utilized to track, first, the distribution of Be between aluminous quartzofeldspathic source rocks and their anatectic melts, and second, the dispersion or concentration of Be in melt through igneous crystal fractionation of different magma types (e.g., S-type, I-type) up to beryl-saturated granitic pegmatites and, finally, into their hydrothermal aureoles. Among the rock-forming minerals, cordierite, calcic oligoclase, and muscovite (in this order) control the fate of Be because of the compatibility of Be in these phases. In general, beryl-bearing pegmatites can arise only after extended crystal fractionation of large magma batches (to F, fraction of melt remaining, ≤0.05); granitic magmas that originate from cordierite-bearing protoliths or that contain large modal quantities of calcic oligoclase will not achieve beryl saturation at any point in their evolution.